The Strategic Partnership of Turkiye and Azerbaijan in Bolstering European Energy Security - ISMAYILZADA, Azer (PEARSON JOURNAL, 2023)
The energy supply of the European Union (EU) countries is provided mainly at the expense of foreign countries. Dependence on foreign countries for a significant part of the provided energy resources is one of the main reasons that push the EU countries to form a common energy policy. A reliable and affordable energy supply is vital for the European economy. However, the European Union countries do not have enough energy resources to meet their needs. Currently, 90 percent of EU countries’ demand for oil and 70 percent of their demand for natural gas are covered by imports. The EU has developed many options for the implementation of energy imports, and work is underway to implement new ones. Oil, one of the main sources of energy, is available in different regions of the world and can be sold and transported around the world flexibly. The supply of natural gas is relatively different and there are problems in this area. So, natural gas is usually imported through pipelines. It takes a lot of time and time to build these types of pipelines, and it takes years to put them into production. Before the start of the Russia-Ukraine war, about 40 percent of EU countries’ natural gas imports were provided by only one supplier - Russia. Even with greater renewable energy supply, imported natural gas will remain the mainstay of the EU’s energy mix for decades to come. Europe is trying hard to find other suppliers to reduce its dependence on Russian gas. Azerbaijan’s natural gas resources, which are transported to European markets through Türkiye, have recently become more relevant in this matter. Azerbaijan has rich hydrocarbon deposits. In general, the volume of Caspian basin oil reserves is 203.2-257.7 billion barrels, of which 39-72 billion barrels belong to Azerbaijan. The volume of confirmed gas reserves of the Caspian region is 232 trillion cubic meters, of which 30 trillion cubic meters belong to Azerbaijan. The volume of gas only in the Shah Deniz field is estimated at 1.4 trillion cubic meters. The Caspian Sea basin is of great geostrategic importance, being of interest to international and regional powers, and the main part of it is Azerbaijan and its natural resources. The current war between Russia and Ukraine has further increased the importance of Caspian hydrocarbon resources in the energy security of Europe. Thus, natural gas supplied from Azerbaijan will have a decisive role in Europe’s energy supply. The embargoes imposed on Russia as a result of the war with Ukraine, as well as the prolongation of the war, give reason to say this.